Wnt signaling recruits KIF2A to the spindle to ensure chromosome congression and alignment during mitosis - Bufe, Anja; García del Arco, Ana; Hennecke, Magdalena; Jaime-Soguero, Anchel de; Ostermaier, Matthias; Lin, Yu-Chih; Ciprianidis, Anja; Hattemer, Janina; Engel, Ulrike; Beli, Petra; Bastians, Holger; Acebron, Sergio P. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Canonical Wnt signaling plays critical roles in development and tissue renewal by regulating β-catenin target genes. Recent evidence showed that β-catenin-independent Wnt signaling is also required for faithful execution of mitosis. However, the targets and specific functions of mitotic Wnt signaling still remain uncharacterized. Using phosphoproteomics, we identified that Wnt signaling regulates the microtubule depolymerase KIF2A during mitosis. We found that Dishevelled recruits KIF2A via its N-terminal and motor domains, which is further promoted upon LRP6 signalosome formation during cell division. We show that Wnt signaling modulates KIF2A interaction with PLK1, which is critical for KIF2A localization at the spindle. Accordingly, inhibition of basal Wnt signaling leads to chromosome misalignment in somatic cells and pluripotent stem cells. We propose that Wnt signaling monitors KIF2A activity at the spindle poles during mitosis to ensure timely chromosome alignment. Our findings highlight a function of Wnt signaling during cell division, which could have important implications for genome maintenance, notably in stem cells.